Development of Audio-Visual Based Pantomime Learning Media in Grade VIII Students at SMP Plus Zainuddin Pamekasan Regency - Munir, M. Misbahul; ., indar Sabri (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
This research aims to increase the appreciation of students’ art, expression, and creativity in the art of pantomime performance. By using the research and development of ADDIE, this research develops effective and efficient learning products. The results of alpha and beta testing show a high level of validity from various points of view. The conclusion highlights the importance of careful planning in the development of audio-visual-based pantomime learning media and emphasizes the integration of media with other learning approaches as a solution to optimize student learning outcomes. This research contributes to the development of innovative and creative learning methods, and is expected to be the foundation for further research in improving the quality of pantomime learning media and creating a more effective and enjoyable learning experience for students. Keywords: Learning Media, Pantomime, Audio-Visual